Analisis pengaruh kinerja keuangan terhadap efektivitas kerja karyawan pada PT.Telkom Tbk periode 2018 sampai 2020 - Suzana, Dara (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This study aims to determine how and how much influence the independent variable (financial performance) has on the dependent variable (performance effectiveness). Based on the results of research carried out using the SPSS 16.00 system, the results obtained that the influence between financial performance on performance effectiveness and the magnitude of the influence was proven by using the linear regression method which stated that the constant value of 4760,978 means that if the NPM (X.1), GPM (X.2), ROE (X.3), ROA (X.4) are 0 then there will be an increase in Work Effectiveness of 10,759.